Performance of K2O/Nb2O5 as a heterogeneous catalyst for biofuel production. Issue 2 (March 2021) - Yani, F T; Husin, H; Darmadi, D; Muhammad, S; Zaki, M; Adrinda, M; Thifal, M
Abstract: The objective of this study was to investigate K2 O/Nb2 O5 as a new potential heterogeneous catalyst for biofuel production. The catalyst was prepared through an impregnation method using K2 CO3 and Nb2 O5 . The K2 O/Nb2 O5 was analyzed by scanning electron microscopy (SEM) and Energy Dispersive X-ray (EDX). The catalyst was tested for biodiesel production. Transesterification was conducted using vegetable oil and methanol on the predetermined operating condition. The highest yield of biofuel was the reach of 98.5% at K2 O loading of 50% on Nb2 O3 and the catalyst loaded of 4 wt.% to oil. In the increasing of potassium loading on Nb2 O3 shows increasing the activity of the catalysts. Potassium, as an active site, plays a vital role in the reaction of vegetable oil and methanol to produce biodiesel. It is a major component and enhance selectivity of the catalyst. Niobium was able to interact well with potassium, and it enhanced the crystallinity and stability of the catalyst. The characteristics of biodiesel, such as density and viscosity, are evaluated to confirm the purpose of catalyst function. The biodiesel characterization showed in the range with SNI standard.